Predictors of inappropriate complementary feeding practice among children aged 6 to 23 months in Wonago District, South Ethiopia, 2017; case control study - Zerihun Berhanu; Taddese Alemu; Dirshaye Argaw (BMC, 2019)
Abstract Background Inappropriate complementary feeding practice could result in child illness, sub-optimal growth and development. Evidence shows a huge burden of inappropriate complementary feeding practice from global to national level. But studies regarding predictors of inappropriate complementary feeding practices were scarce especially in the study area. Therefore, the aim of this study was to determine predictors and community level factors associated with inappropriate complementary feeding practice among children age 6 to 23 months in Wonago district, South Ethiopia. Methods A community based unmatched case-control study design complemented by a qualitative and dietary data was employed among children in Wonago district from April- 07 to June- 06, 2017. A total of 372 study subjects were enrolled to the study by stratified sampling technique. Data were checked, coded and entered to Epi data and exported to SPSS for analysis. Univariate, bivariable and multivariable logistic regressions analyses were applied. A p- value < 0.05 was considered as statistical significant level. Results Paternal household decision making on feeding(AOR = 4.65, 95% CI = (1.69, 12.81)), family priority to elders during feeding(AOR = 2.35, 95% CI = (1.08, 5.14)), absence of nearby health facility(AOR = 4.15, 95% CI = (1.63, 10.55)), unplanned pregnancy (AOR = 3.45, 95% CI = (1.21, 9.85)), missing ANC(AOR = 2.71, 95% CI = (1.48, 4.96)) and missing EPI service utilization (AOR = 2.43, 95% CI = (1.34, 4.38)) were independent predictors of inappropriate complementary feeding practices. Whereas; lack of awareness, short birth spacing practice, poverty and feeding culture were community related factors. The nutrient density of complementary foods were below WHO desired density level except for energy, protein and vitamin C. Conclusions Inappropriate complementary feeding practice was related to household feeding cultures, health service access and utilization and community related factors like awareness, poverty and low birth spacing. Complementary foods were found to have lower nutrient density than desired by WHO. Promoting community's health service utilization and increasing awareness regarding complementary feeding were recommended.